Gender Stereotyping - Morris, Jeanette (Daily Express, 2003)
This article addresses the issue of gender stereotyping in the curriculum choices made by secondary school students in Trinidad and Tobago
Keywords: Secondary school students; Subjects of study; Educational choice; Gender stereotypes; Trinidad and Tobago